ANALYSIS OF THE INFLUENCE OF SOCIAL AND ECONOMIC FACTORS ON THE USE OF CONTRACEPTION AND FERTILITY IN KUTA DISTRICT - Ni Putu Ayu Pitaloka; I Ketut Sudibia (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The population problem is a problem faced by almost all developing countries in the world, including Indonesia, which is the country with the fourth largest population in the world after India, China and the United States. The objectives of this research are 1) Analyzing the direct influence of education level, income, migration status and gender preference on the duration of contraceptive use, 2) Analyzing the direct influence of education level, income, migration status and gender preference on the number of children born alive, and 3) Analyze the indirect influence of education level, income, migration status and gender preference on the number of children born alive through the duration of contraceptive use. This research was conducted in Kuta District. The respondents in this study were 121 EFA samples using a non-probability sampling method. Data analysis techniques use descriptive statistical analysis techniques, path analysis, direct influence testing and indirect influence testing. The research results showed that 1) education level, income level and migration status had a positive and significant effect on the length of use of contraceptives while they had a negative and significant effect on the number of children born alive, 2) gender preference had a negative and significant effect on the length of use of contraceptives while has a positive effect on the duration of contraceptive use, 3) the duration of contraceptive use has a negative and significant effect on the number of children born alive, and 4) education level, income level, migration status and gender preference have an indirect effect on the number of children born alive through duration of use of contraceptives.